2011
DOI: 10.1159/000327143
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Tumors of the Brain: Demographic Pattern over a Ten-Year Period in the Kashmir Valley

Abstract: Brain tumors in children represent the second most frequent tumors in this age group after hematologic malignancies. We highlight the demographic pattern after retrospective analysis of brain tumors in children from geographically and ethnically distinct Kashmir Valley managed in our center between 2000 and 2009. We had a total of 248 pediatric patients with brain tumors. The parameters analyzed were age, gender, location of tumors and histopathological subtypes as well as WHO grade of tumor. We also did a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 38 publications
3
7
0
2
Order By: Relevance
“…Consistent with the vast majority of international studies [11,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30], a slight male predominance of childhood intracranial tumors (M/F = 1.04) was noted in our Egyptian referral center. In this context, Rickert and Paulus [5], in their meta-analysis of 10,582 childhood brain tumors accumulated from 16 international surveys, reported that the M/F ratio was 1.29.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the vast majority of international studies [11,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30], a slight male predominance of childhood intracranial tumors (M/F = 1.04) was noted in our Egyptian referral center. In this context, Rickert and Paulus [5], in their meta-analysis of 10,582 childhood brain tumors accumulated from 16 international surveys, reported that the M/F ratio was 1.29.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the slight IT preponderance seen in the present study (ST/IT = 216/233 = ratio of 0.94), many authors have reported a slight predominance of IT region tumors compared to those of the ST compartment (Sweden, Denmark, Kashmir, Pakistan, Syria, South Africa, USA and Barbados) [11,15,22,23,24,29,30,32]. This includes the meta-analysis of 16 international studies where the ST/IT ratio was 0.92 [5].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with national and international studies reporting a slight male predominance [8] [9]. In similar national studies, males constituted (57%) in previous NCI study [10], and (51.4%) in a larger Kasr Al Aini study [11].…”
Section: Demographic Datasupporting
confidence: 90%
“…In this study it was observed that infratentorial brain tumour (64%) were more common in the children than supratentorials (36%). Nayil et al found that 44.75% were supratentorial and 55.25% were infratentorial 17 . In another study, Ahmed et al showed supratentorial in 33.3% and infratentorial in 66.7% 16 .…”
Section: Discussionmentioning
confidence: 99%